(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2014)
Polycrystalline samples of (Pb1-уCuу)Sr2(Y1-хCaх)Cu2O7-δ, (Pb1212) 0£ x £ 0,3) were prepared to study the influence of Pb/Bi substitution on its physical properties. Ceramic HTSC samples of (Pb1-уCuу)Sr2(Y1-хCaх)Cu2O7-δ, (Pb1212) 0£ x £ 0,3) were synthesized by standart solid-state reaction from the starting materials Bi2O3, PbO, SrCO3, Y2O3, CaCO3 and CuO. In the first stage a mixture of powders taken in stoichiometric ratio calculated carefully grinded in the agate mortar and annealed in porcelain crucibles in a muffle furnace for 48 hours at 900°C in the disappearance of the characteristic absorption bands of CO32_- in IR spectra ( with intermediate grinding ). After that the powder was properly mixed in agate mortars and pressed into pellets. The pellets were sintered for 72 hour at temperatures 850–900°C in air. A second annealing was performed at 750°C in flowing O2 for 8 h. The X-Ray diffraction patterns reveals that all the compounds are crystallized in space group P4/mmm R123 structure and show mainly the formation of the tetragonal Pb1212 phase. Dependence of lattice parameters from the displacement degree x was studied. Change of lattice parameters related to a possible transition Pb2+/Pb4+. It’s adjusted that for solid solutions (Pb1-уCuу)Sr2(Y1-хCaх)Cu2O7-δ, (Pb1212) 0£ x £ 0,3) have superconductivity properties in temperature interval bellow 77–300 K. Our study reveals that superconductivity and structure stabilization in Pb-based are more critical to sintering conditions that other cuprates. The SEM images of the objects under investigation show particles of different shape which have diameter 1 μm. Therefore, findings suggest that with increasing degree of substitution x an increase in the volume of the unit cell is shown that one of the main factors that affect the crystallographic features of this system is the ratio of cations Pb: Cu: Bi.